2020
DOI: 10.1126/sciadv.abc4516
|View full text |Cite
|
Sign up to set email alerts
|

Repeated gain and loss of a single gene modulates the evolution of vascular plant pathogen lifestyles

Abstract: Vascular plant pathogens travel long distances through host veins, leading to life-threatening, systemic infections. In contrast, nonvascular pathogens remain restricted to infection sites, triggering localized symptom development. The contrasting features of vascular and nonvascular diseases suggest distinct etiologies, but the basis for each remains unclear. Here, we show that the hydrolase CbsA acts as a phenotypic switch between vascular and nonvascular plant pathogenesis. cbsA was enriched in genomes of v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 50 publications
(68 reference statements)
2
33
0
Order By: Relevance
“…vascular tissue vs plant parenchyma) ( Niño-Liu et al 2006 ) . Gene gain/loss events have mediated the transition between vascular and non-vascular pathovars ( Gluck-Thaler et al 2020 ). Therefore, other genomic variables ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…vascular tissue vs plant parenchyma) ( Niño-Liu et al 2006 ) . Gene gain/loss events have mediated the transition between vascular and non-vascular pathovars ( Gluck-Thaler et al 2020 ). Therefore, other genomic variables ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous expression of cbsA enabled strains from non-vascular Xanthomonas pathovars to cause vascular disease symptoms. When cbsA was knocked out in some vascular Xanthomonas pathovars, the pathogen was unable to move through the xylem (Gluck-Thaler et al 2020). While this study focused on Xanthomonas translucens, the findings suggest that the presence of this gene in Xcc and its absence from Xcr could be the reason the former is a vascular pathogen and the latter is not.…”
Section: Genomic Analyses Provide Insights Into Mechanisms Of Xcc Virulencementioning
confidence: 75%
“…In a study of over 50 published Xanthomonas genomes representing vascular and non-vascular pathogens, presence of a hydrolase gene, cbsA, was strongly correlated with the ability to invade the vascular tissue (Gluck-Thaler et al 2020). Heterologous expression of cbsA enabled strains from non-vascular Xanthomonas pathovars to cause vascular disease symptoms.…”
Section: Genomic Analyses Provide Insights Into Mechanisms Of Xcc Virulencementioning
confidence: 99%
“…We found that the vast majority (90%; 63/70) of the CDSs listed in Table S2, which were identified or predicted to be virulence and pathogenicity factors for X. fastidiosa [10, 34,36,38,[81][82][83][84], belong either to the core or soft-core genomes. The lack of CDSs in some strains is mostly due to pseudogenization (data not shown).…”
Section: Virulence Factors As Potential Host Specificity Determinantsmentioning
confidence: 99%